A dendritic fullerene-porphyrin dyad - Campidelli, Stephane; Deschenaux, Robert; Swartz, Angela; Rahman, G. M. Aminur; Guldi, Dirk M.; Milic, Dragana; Vazquez, Ester; Prato, Maurizio (My University, 2006)
We describe the synthesis, characterization and photophys. properties of a fullerene deriv. whose structure includes a Zn-porphyrin and a second generation liq.-cryst. (LC) dendrimer. The size of the fullerene and porphyrin units with respect to the size of the LC dendrimer prevents the formation of liq.-cryst. phases. However, this system gives interesting photoinduced electron transfer phenomena. Compd. 1 has been investigated by steady state and time resolved fluorescence as well as transient absorption spectroscopy in polar and apolar solvents. We demonstrate that the fluorescence of the porphyrin unit in 1 is quenched compared to the Zn-tetraphenylporphyrin used as ref. Femto- and picosecond transient absorption permit to identify the formation of a radical ion pair while nanosecond expts. allowed the detn. of the charge recombination lifetimes. [on SciFinder(R)]
Keywords: dendrimer fullerene porphyrin dyad